O ensino de Botânica no ensino médio da rede estadual de São José dos Campos - SP: desafios e possibilidades - Carvalho, Nathalia Gabriela de Souza (2023)
This research aimed to identify the methodologies and teaching tools used by high school biology teachers in classes focused on the study of Botany. Such an objective arises from the fact that the various works that focus on research into the study of Botany demonstrate that there is difficulty in students' understanding and interest in the area. Furthermore, this scenario is closely related to the presence of teaching methodologies that do little to favor the construction of knowledge, the vast majority of which are based on a traditional teaching and learning perspective. Thus, in seeking to understand the teaching strategies, as well as the challenges inherent to the teaching activity in teaching Botany, qualitative research was applied in this study, using a semi-structured interview as a data collection instrument. The participants were 17 teachers, distributed across 10 schools incorporated in the state network in the city of São José dos Campos – SP. To analyze the data obtained, Category Content Analysis was used. The results obtained indicate that teachers see the importance of diversified strategies for teaching Botany. However, the prevalence of methodologies related to traditional teaching models is more evident. Furthermore, there are different obstacles present in public education that do little to contribute to the continuous and in-depth learning of students in the teaching of Botany, which often go beyond the scope of the teachers' work. It is expected that the results obtained with this work, together with the different discussions brought forward, can collaborate with teaching practices since different ways of diversifying Botany were presented throughout the study with the use of resources and instruments that are often not explored by teachers.